New methods for the synthesis of 4H‐dithieno[3, 2‐b:2′, 3′‐d]pyrrole1. (11th July 2017) - Förtsch, Sebastian; Vogt, Astrid; Bäuerle, Peter
Abstract: Various alternative methods for the synthesis of 4 H ‐dithieno[3, 2‐ b :2′, 3′‐ d ]pyrrole (DTP) starting from commercially available bromothiophene precursors are presented. Crucial steps involve the Cadogan reaction, Ullmann‐type C─N couplings, or Buchwald‐Hartwig–type aminations to build up the central pyrrole ring of DTP, respectively. The use of ammonia surrogates afforded the fused target heteroacene in overall yields of 33% to 63%, and the corresponding methods are applicable on large scale. Abstract : Six alternative methods for the synthesis of 4 H ‑dithieno[3, 2‐ b :2′, 3′‐ d ]pyrrole (DTP) are presented involving Cadogan, Ullmann‐type, or Buchwald‐Hartwig–type reactions. The use of ammonia surrogates afforded the fused target heteroacene in overall yields of 33% to 63%, and the corresponding methods are applicable on large scale.